2007
DOI: 10.1002/pmic.200700503
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic identification of tyrosine nitration targets in kidney of spontaneously hypertensive rats

Abstract: Nitrosative and oxidative stress are implicated in the development of hypertension. Events in the renal medulla may play a key role in the development and progression of hypertension. This may arise through disruption of nitric oxide signalling in the medulla and be accompanied by enhanced nitrosative and oxidative stress as indicated by the presence of proteins containing 3-nitrotyrosine. Here we demonstrate enhanced protein nitration in the medulla of spontaneously hypertensive rats. We have identified sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 60 publications
0
27
0
1
Order By: Relevance
“…The medulla is an area that is significant in determining the level at which blood pressure may be set (7) and is a relatively hypoxic area and under oxidative stress (1). This is exacerbated in hypertension as demonstrated in recent proteomic studies in the medulla of the spontaneously hypertensive rat where there was enhanced nitration of proteins involved in NO signaling and antioxidant defense (22) as well as raised carbonylation of enolase 1 and catalase (23). Lenda and Boegehold (14) reported that exposure of rats to a high-salt diet resulted in a raised oxidant activity within the walls of arterioles in the skeletal microvasculature which they attributed to increased NAD(P)H oxidase activity (15).…”
mentioning
confidence: 90%
“…The medulla is an area that is significant in determining the level at which blood pressure may be set (7) and is a relatively hypoxic area and under oxidative stress (1). This is exacerbated in hypertension as demonstrated in recent proteomic studies in the medulla of the spontaneously hypertensive rat where there was enhanced nitration of proteins involved in NO signaling and antioxidant defense (22) as well as raised carbonylation of enolase 1 and catalase (23). Lenda and Boegehold (14) reported that exposure of rats to a high-salt diet resulted in a raised oxidant activity within the walls of arterioles in the skeletal microvasculature which they attributed to increased NAD(P)H oxidase activity (15).…”
mentioning
confidence: 90%
“…These reveal formation of carbonyl groups on residue side chains, tyrosine nitration and glutathionylation [11][12][13] [14,15]. Detection of redox-based modifications in this manner is arguably more informative than mere changes in protein abundance.…”
Section: Electrophoresis-based Detection Of Redox Lesionsmentioning
confidence: 99%
“…Nitrated proteins may be identified in complex biological samples using 2D-PAGE in combination with western blotting with anti-nitrotyrosine antibodies and the identity of the proteins as well as the sites of modification determined by mass spectrometry (MS). However, only few actual nitration sites have been recognized using this approach [22][23][24].…”
Section: Introductionmentioning
confidence: 99%